The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/hbm.25701
|View full text |Cite
|
Sign up to set email alerts
|

The role of the arousal system in age‐related differences in cortical functional network architecture

Abstract: A common finding in the aging literature is that of the brain's decreased within‐ and increased between‐network functional connectivity. However, it remains unclear what is causing this shift in network organization with age. Given the essential role of the ascending arousal system (ARAS) in cortical activation and previous findings of disrupted ARAS functioning with age, it is possible that age differences in ARAS functioning contribute to disrupted cortical connectivity. We test this possibility here using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 78 publications
4
8
0
Order By: Relevance
“…The present study found that the ascending arousal nuclei were positively connected to each other within the AAN. These intranetwork results are consistent with those of recent studies on the FC of ascending arousal nuclei using resting‐state fMRI data (Beissner et al, 2014 ; Guardia et al, 2022 ; Singh et al, 2022 ). In addition, internetwork results showed increased positive FCs of AAN‐DMN, AAN‐CBN, and MRF‐PAG and increased negative FCs of AAN‐SMN and AAN‐DAN in patients with CID compared to GSCs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study found that the ascending arousal nuclei were positively connected to each other within the AAN. These intranetwork results are consistent with those of recent studies on the FC of ascending arousal nuclei using resting‐state fMRI data (Beissner et al, 2014 ; Guardia et al, 2022 ; Singh et al, 2022 ). In addition, internetwork results showed increased positive FCs of AAN‐DMN, AAN‐CBN, and MRF‐PAG and increased negative FCs of AAN‐SMN and AAN‐DAN in patients with CID compared to GSCs.…”
Section: Discussionsupporting
confidence: 91%
“…The present study found that the ascending arousal nuclei were positively connected to each other within the AAN. These intranetwork results are consistent with those of recent studies on the FC of ascending arousal nuclei using resting-state fMRI data (Beissner et al, 2014;Guardia et al, 2022;Singh et al, 2022). In LC, MR, PBC, PO, and PPN were the major nodes that connected the AAN to other resting-state networks.…”
Section: Disruption Of Aan-cortical Network Coupling Patterns In Pati...supporting
confidence: 91%
See 1 more Smart Citation
“…We first demonstrated that function-structure connectivity convergence showed an age-related pattern similar to the pattern of resting-state functional connectivity established in previous literature: within network connections decrease and between network connections increase as age increases (Bethlehem et al, 2020;Betzel et al, 2014;L. Geerligs et al, 2014;Guardia et al, 2022). Overall function-structure connectivity convergence showed stronger correlations with multiple cognitive domains in comparison with functional connectivity observed and function-structure connectivity divergence.…”
Section: Discussionsupporting
confidence: 75%
“…We have proposed that the maintenance of cognitive function with advancing age is increasingly dependent on the integrity of functional brain networks (Tsvetanov et al, 2016). This proposal replicates across cognitive states (Tomassini et al, 2022;Tsvetanov et al, 2018), neuroimaging modalities (Tibon et al, 2021), analytical approaches (Bethlehem et al, 2020;Linda Geerligs & Tsvetanov, 2017;Guardia et al, 2022) and in individuals with genetically increased risk of dementia (Chan et al, 2021;Passamonti et al, 2019;Rittman et al, 2019;Tsvetanov, Gazzina, et al, 2021). However, the increased reliance on functional integrity for maintaining cognitive functions in later life is poorly understood.…”
Section: Introductionmentioning
confidence: 92%